Simulation and model support correction for slotted wall transonic wind tunnels. (1st January 2013) - Heidebrecht, Alexander
Simulating the flow inside a wind tunnel can be useful for many purposes from planning experiments and design of a wind tunnel or components to CFD code validation or correction of wind tunnel measurements. This paper shows a CFD representation of a model plus support in a transonic wind tunnel flow and investigates its usefulness. Based on computational results, conclusions are drawn regarding support interference. The outline for a full support correction method is presented, including model support, mounting effects and buoyancy as well as other interferences due to non-uniform pressure distribution in the test section. The wind tunnel regarded is the European transonic windtunnel (ETW).